Solar Microbial Electrolysis: A Sustainable Solution for Textile Wastewater Treatment and Hydrogen Production Using Aspen Plus Model (Chemical Engineering Research Bulletin, 2026)
The unregulated discharge of textile wastewater has a detrimental effect on soil, air, and water, releasing hazardous contaminants such as dyes, heavy metals, and organic materials into the ecosystem. This study investigated the practical application of solar microbial electrolysis using Aspen Plus. It is an effective method of understanding pilot-scale biohydrogen production. The simulation environment highlights the promise and versatility of solar microbial electrolysis cells. Utilizing 2000 kg of textile wastewater as a substrate, 33.56 kg was produced; this comprehension model also included a hydrogen separation and storage section. The hydrogen storage conditions are optimized at 150 bar and 40°C. This simulation also quantifies the changes in enthalpy and entropy in different stages of the SMEC plant. Maximum enthalpy was observed in the final product of the simulation.Chemical Engineering Research Bulletin: 24 (Issue 1): 129-135